DEVELOPING CULTURAL AWARENESS BY USING BINGO BREAK STRATEGIES TO THE SECOND LANGUAGE CLASSROOM - ILYAS, ILYAS (DIDAKTIKA, 2017)
This research focused more about developing cultural awareness especially in language classroom. Many conflicts happened around us as the effect of lack of different culture awareness. So “cultural discussion” become the important subject in this world and not except for language classroom. But many teachers now assume that culture and language must be taught separately. This of course waste many times and is not effective in teaching both subjects. The purpose of this research is to describe the relevance of culture and language, and offer one strategy to teach culture in language by using bingo break or vice versa.